2020
DOI: 10.3390/genes11060615
|View full text |Cite
|
Sign up to set email alerts
|

Could the Heat Shock Proteins 70 Family Members Exacerbate the Immune Response in Multiple Sclerosis? An in Silico Study

Abstract: Multiple sclerosis (MS) is a chronic autoimmune demyelinating disease of the central nervous system. It represents one of the main causes of neurological disability in young people. In MS, the autoimmune response is directed against myelin antigens but other possible bio-molecular markers are investigated. The aim of this work was, through an in silico study, the evaluation of the transcriptional modifications between healthy subjects and MS patients in six brain areas (corpus callosum, hippocampus, internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Corpus callosum and optic chiasm were the most significantly affected CNS regions in a study, and myelinating oligodendrocytes were most enriched with differentially expressed genes ( 51 ). Heat shock proteins were upregulated in all examined brain regions ( HSPA1A, HSPA1B, HSPA7, HSPA6, HSPH1, HSPA4L ) ( 52 ). Genes important in antigen-presentation, inflammation and hypoxia-induced responses were altered in the corpus callosum and optic chiasm ( TAPBP, IRF4, CTSB, CD79A ), while STAT6 and HLA-DRB5 were only increased in the optic chiasm.…”
Section: Resultsmentioning
confidence: 99%
“…Corpus callosum and optic chiasm were the most significantly affected CNS regions in a study, and myelinating oligodendrocytes were most enriched with differentially expressed genes ( 51 ). Heat shock proteins were upregulated in all examined brain regions ( HSPA1A, HSPA1B, HSPA7, HSPA6, HSPH1, HSPA4L ) ( 52 ). Genes important in antigen-presentation, inflammation and hypoxia-induced responses were altered in the corpus callosum and optic chiasm ( TAPBP, IRF4, CTSB, CD79A ), while STAT6 and HLA-DRB5 were only increased in the optic chiasm.…”
Section: Resultsmentioning
confidence: 99%
“…HSPs are important proteins commonly found as chaperones that mediate the correct assembly of proteins and their intracellular location to protect other proteins against chemical and physical changes in the cytoplasm ( Lanneau et al, 2008 ). HSPs constitute approximately 5–10% of the total protein of all normal unstressed cells, perform many constitutive stabilization state functions, and play an important role in maintaining cell homeostasis ( Chiricosta et al, 2020 ). In stress-free cells, HSPs play various instinctive functions.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoproteomic analysis showed that GroEL and DnaK were among the chaperones in C. jejuni that share high homology with human homologues that may contribute to Guillain-Barré syndrome triggering [ 95 ]. Recently, it was speculated that HSP70 may play a role in the autoimmune disease multiple sclerosis (MS) as genes related to HSP70 were overexpressed in MS patients [ 96 ]. A rather elegant study by Elfaitouri et al demonstrated that there may be cross-reactivity between prokaryotic HSP60 and antibodies derived from patients with the autoimmune disease myalgic encephalomyelitis.…”
Section: Evidence For Adjuvant and Immunomodulatory Potential Of Pmentioning
confidence: 99%